Direct observation of the solvent organization and nuclear vibrations of [Ru(dcbpy)2(NCS)2]4−, [dcbpy = (4, 4′-dicarboxy-2, 2′-bipyridine)], via ab initio molecular dynamics. Issue 40 (18th August 2021) - Perrella, Fulvio; Petrone, Alessio; Rega, Nadia
Abstract : Structural, solvation and vibrational features of the Ru(ii ) complex [Ru(dcbpy)2 (NCS)2 ] 4− (N3 4− ) in water solution have been investigated through ab initio molecular dynamics with a hybrid explicit/implicit solvation model. Abstract : Environmental effects can drastically influence the optical properties and photoreactivity of molecules, particularly in the presence of polar and/or protic solvents. In this work we investigate a negatively charged Ru(ii ) complex, [Ru(dcbpy)2 (NCS)2 ] 4− [dcbpy = (4, 4′-dicarboxy-2, 2′-bipyridine)], in water solution, since this system belongs to a broader class of transition-metal compounds undergoing upon photo-excitation rapid and complex charge transfer (CT) dynamics, which can be dictated by structural rearrangement and solvent environment. Ab initio molecular dynamics (AIMD) relying on a hybrid quantum/molecular mechanics scheme is used to probe the equilibrium microsolvation around the metal complex in terms of radial distribution functions of the main solvation sites and solvent effects on the overall equilibrium structure. Then, using our AIMD-based generalized normal mode approach, we investigate how the ligand vibrational spectroscopic features are affected by water solvation, also contributing to the interpretation of experimental Infra-Red spectra. Two solvation sites are found for the ligands: the sulfur and the oxygen sites can interact on average with ∼4 and ∼3 water molecules, respectively, where a stronger interaction of the oxygen sites is highlighted. On average an overall dynamic distortion of the C 2 symmetric gas-phase structure was found to be induced by water solvation. Vibrational analysis reproduced experimental values for ligand symmetric and asymmetric stretchings, linking the observed shifts with respect to the gas-phase to a complex solvent distribution around the system. This is the groundwork for future excited-state nuclear and electronic dynamics to monitor non-equilibrium processes of CT excitation in complex environments, such as exciton migration in photovoltaic technologies.